#### Answer

a. $x(2x+7)(2x-7)$
b. $2(9x^2+1)(3x+1)(3x-1)$

#### Work Step by Step

a.
$4x^3-49x$
$=x(4x^2-49)$
$=x(2x+7)(2x-7)$
b.
$162x^4-2$
$=2(81x^4-1)$
$=2(9x^2+1)(9x^2-1)$
$=2(9x^2+1)(3x+1)(3x-1)$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

a. $x(2x+7)(2x-7)$
b. $2(9x^2+1)(3x+1)(3x-1)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.